The influence of technology perception, perceived risk, and complaint handling on customer interest in using Internet banking at Bank Syariah Indonesia KCP Sungai Penuh - Rafina, Yeni; Sarmigi, Elex; Syarif, Dafiar; Travilo, Yoga (Journal of Islamic Economics Lariba, 2024)
Introduction Bank Syariah Indonesia actively uses information technology through digital services. However, not all digital services have a large user base, such as Internet banking, which has fewer users than m-banking. Objectives This study analyzed the impact of perceptions of technology, risk, and complaint handling on customer interest in using Internet banking services at Bank Syariah Indonesia KCP Sungai Penuh.Method This study used a quantitative descriptive research design. The study population comprised Bank Syariah Indonesia KCP Sungai Penuh customers. A sample of 100 customers was used to collect data through questionnaires and documentation. The data were analyzed using a Structural Equation Model (SEM) with Smart PLS 3.2.9.Results The results show that perceptions of technology do not significantly influence customer interest in using Internet banking services at Bank Syariah Indonesia KCP Sungai Penuh. Meanwhile, risk significantly influences customer interest, and complaint-handling does not affect customer interest in the service.Implications The findings suggest that Bank Syariah Indonesia KCP Sungai Penuh should increase outreach and promotional efforts to introduce Internet banking to potential customers, increasing their interest and participation in utilizing this service.Originality/Novelty This study contributes to the body of knowledge on risk perception among customers who adopt Internet banking in the Islamic banking sector.